Claude at the beach - Smith, Alex T. (Atlanta, Ga. : Peachtree, 2014)
When Claude the dog and his friend, Sir Bobblysock, decide to have a vacation at the beach, Claude rescues a man from a shark, Sir Bobblysock wins a sand sculpting contest, and both go in search of pirate treasure.
Kirkus Review
Kirkus Review, March 2014
4.3
K-3.
K-3
Keywords: Beaches -- Juvenile fiction; Dogs -- Juvenile fiction; Socks -- Juvenile fiction; Beaches -- Fiction; Dogs -- Fiction; Humorous stories; Socks -- Fiction; Beaches -- Fiction; Dogs -- Fiction; Humorous fiction; Socks -- Fiction